Answer:
![x_1=2; x_2=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/jsd0bf363tldau5kpdyspcvfju4mb59rxc.png)
Explanation:
The square term is
so we expect the complete square to be of the form
.
Let's compare the first degree terms now: we have
on one side and
on the other. That would make
. At this point we have still the second squared term, so we add and subtract
![\frac14 = (\frac12)^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/2bas3j6xvye1ng5tjdn068g810k1fqn61c.png)
Our equation becomes:
![x^2-x+\frac14 -\frac14-2 =0\\(x-\frac12)^2-\frac94=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/9agv17cpnvefbw6a02st8ibpk6jmx4vis7.png)
(the
term comes from rewriting
and adding the terms out of the bracket).
At this point it's just solving the equation:
![(x-\frac12)^2 = \frac94 \rightarrow x-\frac12=\pm\frac32\\x=\frac12\pm\frac32\\x_1=\frac42 = 2; x_2=\fra-\frac22=-1](https://img.qammunity.org/2023/formulas/mathematics/high-school/7y9a45anjaejmpngwt8tfnmo4fjanh1heq.png)